Money Demand in the Arab Republic of Egypt : A Vector Equilibrium Correction Model - Rostom, Ahmed (World Bank, Washington, DC, 2016)
Money demand is critical for defining monetary policy options and is not driven necessarily by developed country standards of transaction demand, speculation motive, and opportunity costs grounded by fully functioning financial markets. However, market imperfections in less developed economies can also play a critical role in the dynamics of demand for money. This paper estimates a vector equilibrium correction model to investigate the nature of short-term and long-term interactions for money demand in the Arab Republic of Egypt. The paper concludes that real money demand in Egypt during (1958-2013) is stable and can be considered confidently by monetary authorities to adjust for long-term growth in the real economy. The rate of devaluation of the official exchange rate and inflation have a serious effect on the public's trust in the national currency in the long term. Money is not neutral for long-term portfolio decisions, because of the increase in real income in the economy that couples with an uptrend in monetization as the ratio of money stock over output also uptrends. The paper also provides quantitative evidence that the devaluation within the parallel market is negatively related to the change in demand for real money balances in the short term. Economic agents hold more domestic currency if the official exchange rate slides, and arbitrage opportunities are sought in the parallel market.